2022
DOI: 10.3390/ijms23158139
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Transport and Nucleobase Uptake Null Mutants in Leishmania mexicana for the Routine Expression and Characterization of Purine and Pyrimidine Transporters

Abstract: The study of transporters is highly challenging, as they cannot be isolated or studied in suspension, requiring a cellular or vesicular system, and, when mediated by more than one carrier, difficult to interpret. Nucleoside analogues are important drug candidates, and all protozoan pathogens express multiple equilibrative nucleoside transporter (ENT) genes. We have therefore developed a system for the routine expression of nucleoside transporters, using CRISPR/cas9 to delete both copies of all three nucleoside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 69 publications
(118 reference statements)
1
12
0
Order By: Relevance
“…However, both surrogates exhibited background nucleoside and nucleotide uptake, thus limiting the extent to which the exogenous transporter can be characterized. Here we used a L. mexicana promastigote line with null nucleoside (NT1.1, NT1.2 and NT2-KO; ‘SUPKO’) or null nucleobase uptake (NT3-KO) as surrogates [ 29 ]. TcoAT1 and each of the four T. vivax ENT family putative nucleoside transporters (TvxNT1–4) and TcoAT1 were PCR-amplified from genomic DNA, cloned into the pNUS-HcN vector, and transfected into SUPKO as described [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both surrogates exhibited background nucleoside and nucleotide uptake, thus limiting the extent to which the exogenous transporter can be characterized. Here we used a L. mexicana promastigote line with null nucleoside (NT1.1, NT1.2 and NT2-KO; ‘SUPKO’) or null nucleobase uptake (NT3-KO) as surrogates [ 29 ]. TcoAT1 and each of the four T. vivax ENT family putative nucleoside transporters (TvxNT1–4) and TcoAT1 were PCR-amplified from genomic DNA, cloned into the pNUS-HcN vector, and transfected into SUPKO as described [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these parasites have developed highly specialized transporters in their membrane for the internalization of the hydrophilic nucleosides from the host environment [ 26 ]. To date, all protozoan purine and pyrimidine transporter genes identified have been of the Equilibrative Nucleoside Transporter (ENT) family [ 25 , 26 , 27 , 28 , 29 , 30 ], although there is a quite strong likelihood that some protozoan purine and/or pyrimidine carriers are expressed by other gene families [ 31 , 32 ]. Where this has been investigated, it was found that the trypanosomatid nucleoside transporters are concentrative proton symporters that exclude uric acid; acidification of the cytosol is prevented by H + -ATPases in the plasma membrane [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,25,26 Additionally, the current wide use of CRISPR/ Cas9 technology for genome editing in Leishmania parasites in combination with its well-defined network of ENT transporters allowed the creation of lineages deficient in the transport of purine nucleosides or nucleobases, which can also be used for the expression and functional characterization of ENT genes from other protozoa. 27 This, combined with the well stablished strategies for drug screening in T. brucei and Leishmania spp., should accelerate the discovery of suitable parasiticidal permeants of the heterologously expressed transporters. However, this does not diminish the need to follow up the initial screening with further testing on the targeted parasite, particularly in organisms phylogenetically distant from the expression system, as it is likely that the intracellular targets differ between species.…”
mentioning
confidence: 99%
“…congolense, Leishmania spp., T. cruzi, Toxoplasma gondii, and Trichomonas vaginalis. ,, Additionally, the current wide use of CRISPR/Cas9 technology for genome editing in Leishmania parasites in combination with its well-defined network of ENT transporters allowed the creation of lineages deficient in the transport of purine nucleosides or nucleobases, which can also be used for the expression and functional characterization of ENT genes from other protozoa . This, combined with the well stablished strategies for drug screening in T.…”
mentioning
confidence: 99%